2021
DOI: 10.3390/antiox10111801
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Microenvironment Stress Promotes the Development of Drug Resistance

Abstract: Multi-drug resistance (MDR) is a leading cause of cancer-related death, and it continues to be a major barrier to cancer treatment. The tumour microenvironment (TME) has proven to play an essential role in not only cancer progression and metastasis, but also the development of resistance to chemotherapy. Despite the significant advances in the efficacy of anti-cancer therapies, the development of drug resistance remains a major impediment to therapeutic success. This review highlights the interplay between var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 346 publications
(527 reference statements)
0
19
0
Order By: Relevance
“…The corresponding model is also based off four key features: cellular heterogeneity, self-renewal, limited plasticity within tumor hierarchy, and drug resistance [209]. The multi-drug resistance phenomenon that currently plagues all cancer therapy is on account of CSCs, induced by endogenous detoxifying enzyme expression, higher levels of drug efflux, decreased drug response, hypoxic stress on the TME, or even increased DNA repair activity [31, [210][211][212][213]. The mechanism of CSC drug resistance is via stem cell pathways.…”
Section: Stem Cell Heterogeneity and Drug Resistancementioning
confidence: 99%
“…The corresponding model is also based off four key features: cellular heterogeneity, self-renewal, limited plasticity within tumor hierarchy, and drug resistance [209]. The multi-drug resistance phenomenon that currently plagues all cancer therapy is on account of CSCs, induced by endogenous detoxifying enzyme expression, higher levels of drug efflux, decreased drug response, hypoxic stress on the TME, or even increased DNA repair activity [31, [210][211][212][213]. The mechanism of CSC drug resistance is via stem cell pathways.…”
Section: Stem Cell Heterogeneity and Drug Resistancementioning
confidence: 99%
“…Exosomal ncRNAs are involved not only in cancer progression and metastasis, but also in treatment resistance development ( 119 ). Obviously, one of the challenges in the treatment of tumor processes during chemoradiotherapy is the development of drug resistance.…”
Section: Possible Functions and Mechanisms Of Exosome-derived Ncrnas ...mentioning
confidence: 99%
“…MDR is a major cause of cancer chemotherapy failure, which can lead to tumor recurrence and the death of cancer patients ( Lage and Dietel, 2000 ). MDR can occur due to 1) the overexpression of certain adenosine triphosphate (ATP)-binding cassette (ABC) transporter proteins ( Robey et al, 2018 ); 2) an increase in the repair of damaged DNA ( Helleday et al, 2008 ); 3) mutations in the target of the anticancer drugs which decrease or abrogate the efficacy of these drugs ( Chandrasekhar et al, 2019 ); 4) an increased tolerance to the stressful tumor microenvironment (TME) ( Erin et al, 2020 ; Seebacher et al, 2021 ); 5) evasion of programmed cell death ( Shahar and Larisch, 2020 ; Neophytou et al, 2021 ); 6) higher levels of reactive oxidative species ( Cui et al, 2018 ); 7) an increase in the biotransformation of the anticancer drugs to less active or inactive metabolites ( Zaal and Berkers, 2018 ); 8) sequestration of drugs by organelles or intracellular molecules that decrease their interaction with their cellular target(s), and 9) specific long noncoding RNAs (lncRNAs) ( Liu et al, 2020 ). Numerous studies have shown that one of the primary mechanisms that mediates MDR in cancer cells is the overexpression of ABCB1 (i.e., P-gp or MDR1), ABCG2 (i.e., BCRP or MXR), and ABCC1 (i.e., MRP1) transporters ( Fletcher et al, 2016 ), which significantly decrease the intracellular levels of certain anticancer drugs by extrusion from cancer cells, thereby decreasing or even abolishing their efficacy ( Wu and Fu, 2018 ).…”
Section: Introductionmentioning
confidence: 99%